Utilization of low sulfur fly ash from circulating fluidized bed combustion burner as geopolymer binder - Antoni Antoni; Stacia Dwi Shenjaya; Maria Lupita; Samuel Santosa; David Wiyono; Djwantoro Hardjito (Institute of Research and Community Outreach - Petra Christian University, 2020)
Circulating fluidized bed combustion (CFBC) is a newer type of burner that employ a circulating process to burn fuel effectively. CFBC burning process is gaining more popularity due to its compact size, high efficiency and lower burning temperature compared to the pulverized coal combustion (PCC) burner. The CFBC burner produces fly ash with different physical properties compared to the PCC burner, i.e. the fly ash is not rounded, and required higher water content for comparable workability. The CFBC fly ash also has a high sulfur content that is detrimental for hardened concrete. Due to its drawbacks, the CFBC hardly used as cementitious material and geopolymer precursor. This study focuses on comparing variations in the concentration of NaOH solution and variations in the ratio of alkaline activators to the setting time and compressive strength of geopolymer mortars on a new class of CFBC fly ash, which have low sulfur content. The concentrations of NaOH solution were 6M, 8M, 10M, and 12M, while the alkaline activator ratios used were 3.0, 2.5, 2.0, 1.0, and 0.5. It was concluded that the low sulfur CFBC fly ash has a potential to be utilized as geopolymer precursor, however, with a shortcoming in its high water demand. The CFBC fly ash used in this study resulted in a geopolymer matrix with good compressive strength and stability. The water demand varies with the fly ash sampling time shows the challenges in the utilization of the fly ash. The highest mortar’s compressive strength, 33.4 MPa at 90 days was achieved at NaOH concentration of 8M and ratio of sodium silicate solution to sodium hydroxide solution of 2.5 with excellent stability.